Teachers' emotion regulation skills facilitate implementation of health-related intentions - Eckert, Marcus; Ebert, David; Lehr, Dirk; Sieland, Bernhard; Jazaieri, Hooria; Berking, Matthias (American Journal of Health Behavior, 2015)
Objectives: Many teachers report high levels of job-related stress. Successful outcomes in stress-management trainings depend on participants actively engaging in skill-building exercises. However, despite good intentions to engage in such exercises on a regular basis, many participants ultimately fail to do so. The present study seeks to understand whether general emotion regulation (ER) skills moderate the relation between the intention to engage in skill-building exercises and actually engaging in these exercises. Methods: ER skills, the intention to engage in autonomous skill-building exercises, and the extent to which individuals actually engaged in such exercises were assessed in a sample of 119 teachers participating in stress-management training. Results: ER skills significantly moderated the association between the intention and engagement in skill-building practice. The greater the ER skills, the more coupled was the relation between the intention and actual practices. Conclusion: Findings are consistent with the hypotheses. Thus, skill-building trainings should support participants scoring low in ER skills in effectively coping with aversive affective states cued through skill-building exercises.
Keywords: Adaptively cope with stress; Emotion regulation; Engaging in health-related intention; Health-behavior; Intention-behaviorgap; Stress-management training